The nomenclature of mts and cpc mutants of Neurospora - D. E. A. CATCHESIDE (Fungal Genetics Reports, 1991)
Mutants defective in general amino acid control in Neurospora have been designated cpc for cross pathway control (Barthelmess 1982, Genet. Res. 39:169-185, Davis 1979, Genetics 93:557-575). More recently, Koch and Barthelmess (1987, FGN 33:30-32, 1988, FGN 35:22-23) have shown that mutants sensitive to 5-methyl tryptophan and designated mts are cpc-1 alleles. Despite the priority of mts, on the grounds of apt description, I propose that the designation mts lapse and cpc be used for this set of alleles.